Less healthy breakfast cereals are promoted more frequently in large supermarket chains in Canada - Potvin Kent, Monique; Rudnicki, Erika; Usher, Crystal (Université d'Ottawa | University of Ottawa, 2017)
Abstract Background The majority of food expenditures are made in supermarkets and this environment influences our purchasing and food intake. Breakfast cereals are frequently marketed as healthy food choices. The objective of this study was to examine the frequency of in–store promotions for cold breakfast cereals in Canadian supermarkets and to determine whether healthier or less healthy breakfast cereals are promoted more frequently. Methods Data was collected once per week over a four-week period from a convenience sample of the five largest Canadian supermarkets in the Ottawa/Gatineau area. Data collection included the number of shelf facings, promotional displays, and the cost of cereals/100 g. The UK Nutrient Profiling Model was used to determine the healthfulness of each breakfast cereal. Results 29.8% (n = 67) of the 225 unique cereals were classified as healthier and 70.2% (n = 158) were classified as less healthy. Less healthy cereals were displayed at eye level, in the profitable middle shelves, 2.9 times more frequently than healthier cereals. There were 5.3 times more breakfast cereal shelf facings, 4.2 more end cap displays, 1.7 more mid-aisle displays and 3.3 more special pricing signage for less healthy cereals compared to healthier cereals. Less healthy cereals had a significantly higher average total number of shelf facings compared to healthier cereals (t = −4.28 (280.8), p < .001). Conclusions Breakfast cereal manufacturers need to consider reformulation of their breakfast cereals to improve their healthfulness and supermarkets need to increase the marketing of healthy breakfast cereals within their stores.